Study on Stakeholders Position and Role in Supply Chain of Cocoa Commodities - Muhammad Asir; Rahim Darma; Mahyuddin Mahyuddin; Muhammad Arsyad (International Journal of Supply Chain Management, 2019)
The quality and continuity of cocoa beans supply is determined really stakeholders in related to the cocoa supply chain. In general, the activity of cocoa beans production has not been efficient yet to compete as raw materials for domestic and foreign industries. In order for cocoa commodities in West Sulawesi province can compete and increase the income of cocoa farmers, so it is necessary to increase the role of main stakeholders and to support the cocoa supply chain especially those support the improvement of cocoa beans productivity. The objective of study is to analyse the position and role of stakeholder in the cocoa bean supply chain. The method used to identify the stakeholders position / structure is Interpretative Structural Modelling (ISM) method, and the role of stakeholders by survey method is to identify the cocoa bean supply chain that becomes the object of research. The results of the study indicate that famers are the most important stakeholders who need to get the attention of other stakeholders in the sustainability of the cocoa supply chain. Marketing institutions (collectors, wholesalers, processing industries, exporters), government / agricultural extension workers, still have few roles in the supply chain of cocoa commodities. The roles as expected of marketing institutions are partnership especially price guarantees and costs support of increasing farmers' garden productivity. The expected roles of governmental extension institution, Non Governmental Organization, college, and banking are to improve the knowledge of farming management through intensive assistance and the capital fulfilment of farmer through soft loan facility, also determining the basic price (minimum price) of cocoa bean among actors who is regulated for and controlled by government.